"It gave me an excuse to get out into society again": Decreasing Veteran Isolation through a Community Agricultural Peer Support Model - Christopher Brown; Karen Besterman-Dahan; Margeaux Chavez; Eni Njoh; William Smith (Journal of Veterans Studies, 2016)
Background: Reintegration is known to be a difficult time for Veterans. Peer support programs offer a good strategy for military and Veterans, particularly as it relates to reintegration.  We review an innovative, peer support program implemented at a Veteran run community agricultural initiative (CAI). Methods: This project was a case-study evaluation using a mixed methods design including participant observations; qualitative interviews with a total of 34 CAI members and affiliates; and administered surveys to a total of 67 CAI members and affiliates. Findings: Survey results suggested that CAI participation contributed to improvements in communication, forming bonds, and developing new friendships with Veterans, non-Veterans, family members, and strangers, as well as increased involvement in community events. Interviews revealed that the CAI’s informal peer-support culture and intentional normalization of sharing stories helped promote recovery and reintegration. Conclusions: The CAI continues to refine its peer support model. The organization is overcoming common barriers by leveraging community partnerships to bring Veterans into the fold and expanding their peer support model to Veteran organizations with similar missions. This will ultimately lead to a culture of peer support across agencies and spread the reach of the CAI’s mission for Veterans.